DIVERSIFICATION OF VEGETABLE OIL DERIVATES VIA OLEFIN METATHESIS REACTION USING RUTHENIUM CATALYST - ARDATUL PUTRA, ILHAM
Palm industry is Indonesian's highest export from agricultural sector over the last decade. Its production reaches 45% which is 36.8 million tons of worldwide palm oil production. This production increases continuously and it is estimated that it will reach 40 million tons in 2020. Palm oil production in Indonesia is still dominated by exporting in crude palm oil whose price is always fluctuating. That is why it is important to derivatize palm oil products to increase its economic value. One of the major component in palm oil is oleic acid (36-44%) that has internal double bond (olefin). This internal double bond in the molecule can be exploited to produce a number derivates by undergoing homo or hetero olefin metathesis reaction. Olefin metathesis reaction is a catalytic reaction that involves exchanging between alkene side groups. By reacting the ester of oleic acid via olefin metathesis, 9-decenoate acid can be produced. This compound is one of the building block to produce drugs, food additives, lubricans oils, herbicides, perfumes, pheromones, coatings, and smart materials. Accodring to Sigma Aldrich catalog, the price of 9-decenoate is around 56 million IDR/L which is a significant increase from the palm oil price. In this research, homo and hetero metathesis reaction of the ester of oleic acid ware carried out using Grubbs II catalyst. Hetero olefin metathesis reaction used ethylene as the reagent. Oleic acid ester was synthesized using methanol and sulfuric acid catalyst with 99% of yield. Ester product has Z configuration which is similar with its oleic acid. Homo olefin metathesis reaction produced 9-Oktadecene and dimethyl 9-Oktadecenoate with 26% and 25% of yield respectively and hetero olefin metathesis reaction produced methyl 9-decenoate with 50% of yield. The products were analyzed using NMR spectroscopy. Homo reaction product was found in mixed form of its E/Z geometry with E:Z ratio at 4:1. Based on that data, changes of alkene configuration were observed. The initial ester substrate has Z configuration that changed into E configuration when it formed the products of homo olefin metathesis. This indicates that homo olefin metathesis reaction produce more E products. The optimized condition for homo olefin metathesis reaction, was achieved at 75oC, 9 hours reaction time, toluene as solvent with the concentration of 1 M in the present of 0,2% mol Grubbs II catalyst. Furthermore dimethyl 9-oktadecendioate was reacted via Dieckmann's cyclization reaction to produce civeton precursor which is the active ingredients of male perfumes. Dieckmann's cyclization reaction is an intramolecular ring formation between carbon alpha with carbonyl in basic condition. This reaction produced two products which were 9-oktadecendioate acid and 2- Methoxycarbonyl-9- cycloheptadecenon with 35% and 25% of yield respectively.